Fatal accidental lipid overdose with intravenous composite lipid emulsion in a premature newborn: a case report - Maliha Badr; Marion Goulard; Bénédicte Theret; Agathe Roubertie; Stéphanie Badiou; Roselyne Pifre; Virginie Bres; Gilles Cambonie (BMC, 2021)
Abstract Background Tenfold or more overdose of a drug or preparation is a dreadful adverse event in neonatology, often due to an error in programming the infusion pump flow rate. Lipid overdose is exceptional in this context and has never been reported during the administration of a composite intravenous lipid emulsion (ILE). Case presentation Twenty-four hours after birth, a 30 weeks' gestation infant with a birthweight of 930 g inadvertently received 28 ml of a composite ILE over 4 h. The ILE contained 50% medium-chain triglycerides and 50% soybean oil, corresponding to 6 g/kg of lipids (25 mg/kg/min). The patient developed acute respiratory distress with echocardiographic markers of pulmonary hypertension and was treated with inhaled nitric oxide and high-frequency oscillatory ventilation. Serum triglyceride level peaked at 51.4 g/L, 17 h after the lipid overload. Triple-volume exchange transfusion was performed twice, decreasing the triglyceride concentration to < 10 g/L. The infant's condition remained critical, with persistent bleeding and shock despite supportive treatment and peritoneal dialysis. Death occurred 69 h after the overdose in a context of refractory lactic acidosis. Conclusions Massive ILE overdose is life-threatening in the early neonatal period, particularly in premature and hypotrophic infants. This case highlights the vigilance required when ILEs are administered separately from other parenteral intakes. Exchange transfusion should be considered at the first signs of clinical or biological worsening to avoid progression to multiple organ failure.